Exploring the Effect of Equitable Teaching Strategy on Perseverance in Solving Mathematical Problems: A Qualitative Study - Alotaibi, Mohammed Nejer; Alharbi, Mohammed Sanat (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to investigate how a teaching strategy based on equitable teaching practices influences perseverance in mathematical problem-solving among ninth-grade students in Taif during the third semester of the year 1445 AH. To achieve the research objectives, a qualitative methodology was adopted using thematic analysis. Individual interviews were conducted with a selected sample of students who participated in the instructional intervention utilizing the specified teaching strategy. The qualitative findings revealed key themes regarding students’ perceptions of the impact of the strategy on mathematical perseverance. The importance of external factors, such as conceptual scaffolding and a supportive teacher’s approach, emerged alongside internal factors like experience gained from repeated practice and the adoption of simplification and representation strategies. Indicators of perseverance included initiating challenging problems, exploring diverse solution methods, and evaluating outcomes. The main challenges identified were task difficulty surpassing students’ abilities and the lack of documentation of solution plans. Based on these findings, the study recommends training teachers to implement equitable teaching strategies, developing mathematical activities that enhance students’ perseverance, and creating a learning environment that supports a growth mindset both teachers and students. The study also suggests conducting future research to explore other dimensions of the investigated variables.